Coagulation Studies Are Not Predictive of Hematological Complications of COVID-19 Infection - Hadique, Sarah; Badami, Varun; Sangani, Rahul; Forte, Michael; Alexander, Talia; Goswami, Aarti; Garrison, Adriana; Wen, Sijin (TH Open, 2022)
Objectives Thrombotic and bleeding complications are common in COVID-19 disease. In a prospective study, we performed a comprehensive panel of tests to predict the risk of bleeding and thrombosis in patients admitted with hypoxic respiratory failure due to severe COVID-19 infection.Methods We performed a single center (step down and intensive care unit [ICU] at a quaternary care academic hospital) prospective study. Sequentially enrolled adult (≥18 years) patients were admitted with acute hypoxic respiratory failure due to COVID-19 between June 2020 and November 2020. Several laboratory markers of coagulopathy were tested after informed and written consent.Results Thirty-three patients were enrolled. In addition to platelet counts, prothrombin time, and activated partial thromboplastin time, a series of protocol laboratories were collected within 24 hours of admission. These included Protein C, Protein S, Antithrombin III, ADAMTS13, fibrinogen, ferritin, haptoglobin, and peripheral Giemsa smear. Patients were then monitored for the development of hematological (thrombotic and bleeding) events and followed for 30 days after discharge. Twenty-four patients (73%) required ICU admissions. At least one laboratory abnormality was detected in 100% of study patients. Nine patients (27%) suffered from significant hematological events, and four patients had a clinically significant bleeding event requiring transfusion. No significant association was observed between abnormalities of coagulation parameters and the incidence of hematologic events. However, a higher SOFA score (10.89 ± 3.48 vs. 6.92 ± 4.10, p = 0.016) and CKD (5/9 [22.2%] vs. 2/24 [12.5%] p = 0.009) at baseline were associated with the development of hematologic events. 33.3% of patients died at 30 days. Mortality was similar in those with and without hematological events. Reduced ADAMTS13 level was significantly associated with mortality.Conclusion Routine extensive testing of coagulation parameters did not predict the risk of bleeding and thrombosis in COVID-19 patients. Thrombotic and bleeding events in COVID-19 patients are not associated with a higher risk of mortality. Interestingly, renal dysfunction and a high SOFA score were found to be associated with increased risk of hematological events.
Keywords: COVID-19; thrombosis; bleeding; ADAMTS-13; 30-day mortality